TIM-3 pathway dysregulation and targeting in cancer. Issue 5 (4th May 2021) - Zeidan, Amer M; Komrokji, Rami S; Brunner, Andrew M
ABSTRACT: Introduction: Dysfunction of the immune system is a hallmark of cancer. Through increased understanding of the complex interactions between immunity and cancer, immunotherapy has emerged as a treatment modality for different types of cancer. Promising activity with immunotherapy has been reported in numerous malignancies, but challenges such as limited response rates and treatment resistance remain. Furthermore, outcomes with this therapeutic approach in hematologic malignancies are even more limited than in solid tumors. T-cell immunoglobulin domain and mucin domain 3 (TIM-3) has emerged as a potential immune checkpoint target in both solid tumors and hematologic malignancies. TIM-3 has been shown to promote immune tolerance, and overexpression of TIM-3 is associated with more aggressive or advanced disease and poor prognosis. Areas covered: This review examines what is currently known regarding the biology of TIM-3 and clinical implications of targeting TIM-3 in cancer. Particular focus is given to myeloid malignancies. Expert opinion: The targeting of TIM-3 is a promising therapeutic approach in cancers, including hematologic cancers such as myeloid malignancies which have not benefited much from current immunotherapeutic treatment approaches. We anticipate that with further clinical evaluation, TIM-3 blockade will emerge as an important treatment strategy in myeloid malignancies.